2018
DOI: 10.1097/md.0000000000011799
|View full text |Cite
|
Sign up to set email alerts
|

Suprapatellar versus infrapatellar intramedullary nailing for treatment of tibial shaft fractures in adults

Abstract: Background:Numerous studies have compared suprapatellar (SP) nailing to infrapatellar (IP) nailing for treatment of tibial shaft fractures; however, the best strategy remains controversial. The aim of this meta-analysis is to assess whether SP or IP nailing is more effective for tibial shaft fractures in adults.Methods:Literature searches of PubMed, Embase, OVID, Cochrane Library, Web of Science, Chinese Biomedical Literature, Wanfang, Weipu Journal, and CNKI databases were performed up to July 2017. Only rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 20 publications
(31 reference statements)
0
31
0
5
Order By: Relevance
“…These findings are confirmed by Sun Q et al who reported a mean operation time of 71.01 min and an intraoperative blood loss of 22.11 ml for SP IMN, showing no difference compared to IP IMN with operation time of 73.26 min and intraoperative blood loss of 21.67 ml. Chen X et al conducted a meta-analysis of RCTs and reported that there were no significantdifferences in the operative time and blood loss between SP and IP groups[19]. However, review analysis of RCTs indicated that SP IMN could significantly reduce total blood loss compared to IP IMN[20].…”
mentioning
confidence: 99%
“…These findings are confirmed by Sun Q et al who reported a mean operation time of 71.01 min and an intraoperative blood loss of 22.11 ml for SP IMN, showing no difference compared to IP IMN with operation time of 73.26 min and intraoperative blood loss of 21.67 ml. Chen X et al conducted a meta-analysis of RCTs and reported that there were no significantdifferences in the operative time and blood loss between SP and IP groups[19]. However, review analysis of RCTs indicated that SP IMN could significantly reduce total blood loss compared to IP IMN[20].…”
mentioning
confidence: 99%
“…In accordance with other studies, the present study revealed comparable operation time and blood loss between SP IMN and IP IMN. RCTs and reported that there were no significant differences in the operative time and blood loss between SP and IP groups [19]. However, review analysis of RCTs indicated that SP IMN could significantly reduce total blood loss compared to IP IMN [20].…”
Section: Resultsmentioning
confidence: 99%
“…No additional complications with the use of the suprapatellar approach had been proven in the literature. [10][11][12][13] Crossing the non-union site is difficult in some cases. It is necessary to have specialised equipment available in the form of solid flexible reamers.…”
Section: Discussionmentioning
confidence: 99%
“…The suprapatellar approach allows insertion of the nail in an extended knee, which aids correction of malalignment in the sagittal and coronal planes. [10][11][12][13] It also creates a straight working channel, allowing the passage of rigid, straight reamers to cross the nonunion site, facilitating IMN for shaft non-unions not previously treated with IMN. Currently there is no literature available on the use of this technique to treat non-unions of the tibia.…”
Section: Introductionmentioning
confidence: 99%